Valorization of Pb 340 rubberwood into liquid smoke as an alternative latex coagulant for Ribbed Smoked Sheet - Manikharda; Ronny Kristian Sembiring; Djagal Wiseso Marseno; Diah Puspitasari (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2025)
Formic acid, commonly used as a coagulant, has been criticized for its adverse environmental impact, leading to the search for sustainable alternatives. Additionally, the rubber processing industry generates a significant amount of unproductive rubber wood during replanting. A promising path to environmental sustainability is to utilize this potential for liquid smoke production. This study examines the use of liquid smoke from rubber wood Clon PB 340 as a latex coagulant and its effect on RSS quality. The findings indicate that RSS adhered to the P0 standard criteria for all tested liquid smoke concentrations. The 5% liquid smoke introduction to RSS, stored for 7 days, achieved the SRI 5 standard. Additionally, liquid smoke additions effectively managed dirt content, meeting or surpassing control criteria at concentrations of 5%, 20%, and 25%. Although the volatile matter content occasionally met SRI 5 standards at specific concentrations (10%, 15%, 20%, and 25%), the ash content across all treatments, including the control, did not meet the SRI 5 quality benchmarks. Using liquid smoke from non-productive rubber wood Clon PB 340 as a natural coagulant holds promise for eco-friendly latex processing. This study may advance the rubber industry's adoption of liquid smoke, promoting higher-quality, environmentally sustainable products.